2015
DOI: 10.1530/erc-15-0094
|View full text |Cite
|
Sign up to set email alerts
|

Defects of the Carney complex gene (PRKAR1A) in odontogenic tumors

Abstract: The surgical treatment of some odontogenic tumors often leads to tooth and maxillary bone loss as well as facial deformity. Therefore, the identification of genes involved in their pathogenesis may result in alternative molecular therapies. The PRKAR1A gene shows loss of protein expression, as well as somatic mutations in odontogenic myxomas, an odontogenic ectomesenchymal neoplasm. We used a combination of qRT-PCR, immunohistochemistry, LOH analysis and direct sequencing of all PRKAR1A exons to assess if this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Identifying pathogenic genes may enable molecular treatments, preventing deformities resulting from surgery. 10…”
Section: Discussionmentioning
confidence: 99%
“…Identifying pathogenic genes may enable molecular treatments, preventing deformities resulting from surgery. 10…”
Section: Discussionmentioning
confidence: 99%
“…PRKAR1A protein insufficiency and PKA dysregulation have been implicated in various types of disorders, including Albright hereditary osteodystrophy (AHO), pseudohypoparathyroidism (PHP), acrodysostosis (ACRDYS)8, and Carney complex9. Interestingly, recent studies also showed that PRKAR1A protein expression level was significantly dysregulated in multiple primary carcinomas and distant metastases, such as cardiac myxomas10, odontogenic myxomas11, anaplastic thyroid carcinomas12, breast cancer13, pediatric pituitary adenomas14, and Schwann cell tumors15.…”
mentioning
confidence: 99%